Emission characteristics of a charged‐droplet beam source using vacuum electrospray of an ionic liquid. (15th June 2012) - Fujiwara, Yukio; Saito, Naoaki; Nonaka, Hidehiko; Ichimura, Shingo
<x xml:space="preserve">Abstract</x> To develop an ion source capable of producing a charged‐droplet beam at higher current density with a smaller beam spot size, beam characteristics of electrosprayed charged particles were investigated. A quaternary ammonium ionic liquid, N, N‐diethyl‐N‐methyl‐N‐(2‐methoxyethyl)ammonium bis(trifluoromethanesulfonyl) amide (DEME‐TFSA), was tested in vacuum around 10−5 Pa. A hysteresis behavior in the electrosprayed current was observed when the capillary voltage was changed. The m/z values of generated charged droplets decreased with decreasing flow rate and increasing capillary voltage and temperature. Average masses and charge numbers of the charged droplets as well as projectile energy per nucleon were estimated on the basis of the experimental results. Copyright © 2012 John Wiley & Sons, Ltd.